2014
DOI: 10.1097/mnm.0000000000000014
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential of [11C]choline-PET/CT as a novel imaging biomarker for predicting early treatment response in prostate cancer

Abstract: This feasibility study shows that [C]choline-PET/CT detects metabolic changes within tumours following NAD and RT-CAD to the prostate. A differential reduction in [C]choline uptake despite a global reduction in PSA following NAD and RT-CAD could provide prognostic information and warrants further evaluation as an imaging biomarker in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 26 publications
(21 reference statements)
3
18
0
Order By: Relevance
“…Single case reports or small case series have been reported that suggest 18F-NaF and 11C-choline may be useful in the assessment response to Ra-223 dichloride therapy [49, 50]. Similar preliminary results have been reported for effects of neodjuvant androgen deprivation and radical prostate radiotherapy with concurrent androgen deprivation therapy on uptake level of 11C-choline in tumors [51, 52]. There is currently no experience with other PET radiotracers in the clinical setting of treatment response assessment in patients with prostate cancer.…”
Section: Treatment Response Evaluation and Prognosticationmentioning
confidence: 68%
“…Single case reports or small case series have been reported that suggest 18F-NaF and 11C-choline may be useful in the assessment response to Ra-223 dichloride therapy [49, 50]. Similar preliminary results have been reported for effects of neodjuvant androgen deprivation and radical prostate radiotherapy with concurrent androgen deprivation therapy on uptake level of 11C-choline in tumors [51, 52]. There is currently no experience with other PET radiotracers in the clinical setting of treatment response assessment in patients with prostate cancer.…”
Section: Treatment Response Evaluation and Prognosticationmentioning
confidence: 68%
“…Gebhart et al reported that, in 86 HER2-positive breast cancer patients, only 77 patients had an evaluable baseline signaling using (18)F-FDG PET/CT scans [43]. FDG-PET/CT cannot reliably detect tumors <0.5 cm in size and, thus, cannot reliably detect emerging metastasis in tumors that acquire resistance to targeted drugs and undergoing metastasis [44, 45]. Timely monitoring of the onset of disease recurrence or the emergence of secondary resistance to targeted drugs continues to be a major challenge.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred paraffin-embedded malignant prostate tumour cores (including 20 cores from patients whose primary and IHC data have been previously published,20 and 10 cores from patients recruited to the choline response study19) and 25 normal prostate cores were analysed. The 70 malignant cores were obtained from consecutive patients who had neoadjuvant androgen deprivation and radical radiotherapy for their prostate cancer.…”
Section: Methodsmentioning
confidence: 99%